DATA CRAWLING USING RAPIDMINER ON TWITTER - Komara, Diemas Arya (Perpustakaan Universitas Muhammadiyah Ponorogo, 2022)
Twitter is one of the social media that is favored by various groups, Twitter itself can display information in the form of textual information which can be supplemented with videos or images. This study will discuss how to crawl data on Twitter social media, using the Rapidminer application, 10000 data can be retrieved in one operation. This study aims to provide knowledge about how to use Rapidminer programming to obtain data that can later be processed for purposes related to information science. The results of this study are to show how to collect data on Twitter social media quickly using text mining.